SISTEM INFORMASI BOOKING VILLA GUNUNG GARE DI KOTA PAGAR ALAM BERBASIS WEB - Apriansyah Apriansyah; Desse karan Prayoga putri; Jimmie Jimmie (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
The rapid development of information technology has had a major impact on various aspects of life, including the delivery of information and marketing. Information technology allows more efficient data processing through the use of computers and software, with its application in various sectors, such as websites for marketing. One example of the application of information technology is the online villa booking system. This journal focuses on designing an online villa booking system, which aims to simplify the villa booking process without having to come directly to the location. This study uses the Waterfall method for system development and applies Unified Modeling Language (UML) in its design. Along with the development of technology in everyday life in order to convey information, various media are needed to help disseminate it. As a case study, Gunung Gare Villa in Pagar Alam, South Sumatra, which has great tourism potential but still uses a manual booking system, is the focus. main topic of this research. With the proposed online booking system, it is hoped that it can increase the efficiency and convenience of visitors in booking villas, while supporting a more effective marketing strategy